2009 International Conference on Networks Security, Wireless Communications and Trusted Computing 2009
DOI: 10.1109/nswctc.2009.130
|View full text |Cite
|
Sign up to set email alerts
|

C-MAC: A TDMA-Based MAC Protocol for Underwater Acoustic Sensor Networks

Abstract: Different from terrestrial wireless networks that use radio channel, underwater networks utilize acoustic channel, which poses great research challenges in medium access control (MAC) protocol design due to its low available bandwidth and high propagation delay characteristics. In addition, the high bit-error, high transmission energy cost, and complex multi-path effects in underwater environment make it even harder. In this paper, a suitable MAC protocol, named C-MAC (cellular MAC) for underwater acoustic sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Fan et al [112] designed an SDN-based AUV system and implemented a test bed on WaterCom [113], in which the performance of the slotted FAMA [114] and UW-ALOHA [115] is tested and compared. Ghafoor and Koo [116] considered the natural and artificial acoustic systems as the two Primary Users (PUs) of UASNs and designed an SDN-based architecture in which buoys are treated as the Main Controllers (MCs) to maintain the global view of the network.…”
Section: Underwater Acoustic Sensor Network Based On Sdnmentioning
confidence: 99%
“…Fan et al [112] designed an SDN-based AUV system and implemented a test bed on WaterCom [113], in which the performance of the slotted FAMA [114] and UW-ALOHA [115] is tested and compared. Ghafoor and Koo [116] considered the natural and artificial acoustic systems as the two Primary Users (PUs) of UASNs and designed an SDN-based architecture in which buoys are treated as the Main Controllers (MCs) to maintain the global view of the network.…”
Section: Underwater Acoustic Sensor Network Based On Sdnmentioning
confidence: 99%
“…Yutao Ma and et al [3] they have suggested in their paper that the the high bit-error, high transmission energy cost, and complex multi-path effects in underwater environment make it even harder. In this paper, a suitable MAC protocol, named C-MAC (cellular MAC) for underwater acoustic sensor networks (UWANs) is proposed.…”
Section: Litrature Surveymentioning
confidence: 99%
“…C-MAC is a synchronous TDMA-based protocol for multi-hop underwater networks, which divides networks into many cells. A time slot is assigned to each cell; nodes in a cell can only transmit packets in the given time slots [27]. This protocol utilizes channel division with different time stamps, which alleviates the detrimental effect of long propagation delays on network throughput.…”
Section: Previous Workmentioning
confidence: 99%